Un modelo explicativo de los niveles de adopción de comercio electrónico en MiPyMes de Córdoba, Argentina - Alderete, María Verónica; Jones, Carola; Motta, Jorge; González Kriegel, Bernardo (2022)
Fil: Alderete, María Verónica. Universidad Nacional del Sur; Argentina.